The Selected Prose "Dreams" by the Spanish Writer Quevedo: La Miscelánea de "Los Sueños" de Francisco de Quevedo (Journal of the College of Languages (JCL), 2019)
Francisco de Quevedo is a well-known man of letters in the Golden Age of Spanish literature. He is the witness who related to us, in his works, the Spanish community in that era. He showed in most of his writings the political weakness of Spain, and made prominent the remarkable literary aspect of Spain. He had a very good tlent for poetry, and a rather polite style in exploiting colloquialisms in his literary writings. He wrote about philosophy, where his most prominent work was "The cradle and the grave". The writer was also very well-known for his puns which were employed to clarify his inner thoughts regarding the Spanish situation at that time.Resumen El presente estudio explica la producción de uno de los literatos mas celebres de la literatura española , Francisco de Quevedo , sus creatividades en los géneros literarios, la prosa y la poesía. Además de dar una breve visión sobre su obra máxima en la prosa “Los Sueños” en que utilizó un juego de refinado y juego de palabras. Además de dar una breve visión sobre sus obras teológicas filosóficas como la cuna y la sepultura , y sus obras que se caracterizan por juego de palabras de conceptos. His selected prose work "Dreams" is considered an international work. He used terms reflecting the Spanish literary and political situation. This work was written in 1627, and it seemed similar to what was written by international writers in Europe.In this paper, we made a reference to his literary works which belong to various species of literature; also, the paper sheds light on his work (Selected Prose Work "Dreams").